2018
DOI: 10.4103/0366-6999.235872
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance and Interobserver Consistency of the Prostate Imaging Reporting and Data System Version 2

Abstract: Background:One of the main aims of the updated Prostate Imaging Reporting and Data System Version 2 (PI-RADS v2) is to diminish variation in the interpretation and reporting of prostate imaging, especially among readers with varied experience levels. This study aimed to retrospectively analyze diagnostic consistency and accuracy for prostate disease among six radiologists with different experience levels from a single center and to evaluate the diagnostic performance of PI-RADS v2 scores in the detection of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…This may limit the applicability of our results for single readers in clinical practice. Reports indicate that inter-reader reproducibility of PI-RADS v2 tends to be moderate and experience dependent [29, 30]. We would therefore expect that expert single readers would have similar performance to that reported in the present study.…”
Section: Discussionsupporting
confidence: 78%
“…This may limit the applicability of our results for single readers in clinical practice. Reports indicate that inter-reader reproducibility of PI-RADS v2 tends to be moderate and experience dependent [29, 30]. We would therefore expect that expert single readers would have similar performance to that reported in the present study.…”
Section: Discussionsupporting
confidence: 78%
“…One study reported that good interobserver agreement rates use the most appropriate analysis (AC1 = 0.71) and moderate use kappa analysis (kappa = 0.43) [17]. Few studies reported good interobserver agreement using PI-RADS V2 with a remarkable effect on the radiologist's prior experience [19][20][21][22][23][24]. In our work, we found an excellent interobserver agreement using PI-RADS-v2 in reporting MP-MRI for prostate lesions.…”
Section: Discussionsupporting
confidence: 49%
“…The main target is to build acceptable technical standards for prostate mp-MRI, which makes it clear and simpler with subsequent standardized reporting terms, as well as help the procedure of MRI-guided biopsy. It also develops assessment groups that summarize ranks of the risk that could be helpful to choose and prepare patients for the next steps in management and finally enhance interdisciplinary communications with physicians [6,[9][10][11][12][13][14][15][16][17][18][19]. Having both targeted and systematic biopsy could offer the peak discovery of clinically significant prostate cancer [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Greer et al [74] reported excellent agreement on index lesion identification (k = 0.87) and moderate agreement on individual PI-RADS v2 category assignment (k = 0.419). Other two welldesigned studies [75,76] reported similar results, with an area under the curve (AUC) for PCa ranging between 0.88 and 0.95 among six blinded readers [75]. Conversely, two recent studies showed high variability in PI-RADS v2 reporting [77,78].…”
Section: 6mentioning
confidence: 82%